Determinants of Satisfaction Using Healthcare Application: A Study on Young Halodoc Users in Jakarta During the COVID-19 Pandemic - Michael Christian; Eko Retno Indriyarti; Sunarno Sunarno; Suryo Wibowo (Applied Quantitative Analysis, 2022)
Fear of COVID-19 makes people seek information about health protection independently, which is closely related to user satisfaction. This condition makes the need for a series of online applications such as Halodoc a necessity that is increasingly used. People are looking for various information from online health services during the pandemic, ranging from information on personal protection from COVID-19, online consultations with doctors, to ordering drugs or supplements online. This study aims to investigate whether graphic user interface and reliance on use affect the satisfaction of using Halodoc during the COVID-19 pandemic, especially among young users in Jakarta. This quantitative research uses Structural Equation Modeling based on Partial Least Square (PLS-SEM) analysis with SMART PLS 3.0. The sample size of this study was 126 participants taken randomly using an online questionnaire. The results of this study explained that the graphic user interface does not affect the user's reliance on use and satisfaction. Interestingly, the reliance on use affects user satisfaction. In addition, the role of reliance of use is not proven to be a mediator between the graphic user interface on user satisfaction. Originality in this study itself lies in the use of graphic user interface and reliance on use. This is important because these two aspects can represent aspects of user behavior and the quality of the digital-based health service system itself.